2018
DOI: 10.1080/13488678.2018.1536817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altering three phonetic features on intelligibility of English as a lingua franca: a Malaysian speaker and Swedish listeners

Abstract: Our previous study examined the mutual intelligibility of Malaysian English to Swedish listeners and Swedish English to Malaysian listeners. The results showed that Swedish listeners did not understand the Malaysian speaker well. In the present study, the Malaysian speaker was trained to alter her realization of the word stress, consonant clusters and long vowels in a way that previous research has found intelligible for both native and nonnative English speakers. The audible and measurable alteration signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In this connection, it could be suggested that LFC investigations of an experimental (instead of a purely observational) nature are clearly called for; experimental manipulation may guard, to some degree at least, against these confounding analyses. An apropos study in this regard was carried out by Jeong, Thorén, and Othman (2020), who looked into the intelligibility between Malaysian English and Swedish English. Manipulating three phonetic characteristics, word stress, consonant clusters and vowel length, they found that word stress, a non-core feature of the LFC, had an impact on lingua franca intelligibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this connection, it could be suggested that LFC investigations of an experimental (instead of a purely observational) nature are clearly called for; experimental manipulation may guard, to some degree at least, against these confounding analyses. An apropos study in this regard was carried out by Jeong, Thorén, and Othman (2020), who looked into the intelligibility between Malaysian English and Swedish English. Manipulating three phonetic characteristics, word stress, consonant clusters and vowel length, they found that word stress, a non-core feature of the LFC, had an impact on lingua franca intelligibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, by focusing only on a couple of privileged English accents, the teaching of listening seems to keep learners from developing their knowledge of and ability to understand diverse accents. An indication of this are the iterative reports about the misunderstandings or communication breakdowns among L2 speakers caused by accent features distant from GA or RP (e.g., Field, 2005;Deterding, 2013;Kim and Billington, 2016;Jeong et al, 2020). Moreover, only learning to listen to a few native pronunciations seems to lead learners to develop negative attitudes toward "other" accents.…”
Section: Are English Learners Taught To Be Good Listeners Of Global Englishes Accents?mentioning
confidence: 99%
“…Intelligibility, comprehensibility, accentedness, and acceptability are constructs that have been operationalized to evaluate L2 speakers pronunciation against a listener's understanding and perception . Often, listener judges are native speakers (e.g., Munro and Derwing, 2006;Kennedy and Trofimovich, 2008) and more recently also L2 speakers (e.g., Jeong et al, 2020). While intelligibility, comprehensibility, and accentedness have been extensively adapted since Munro and Derwing's seminal studies (e.g., Munro and Derwing, 1995a;Munro and Derwing, 1995b), acceptability is a relatively new construct for measuring listeners negative or positive attitudes toward perceived accentedness (e.g., Szpyra-Kozlowska, 2014;Tulaja, 2020).…”
Section: Are English Learners Taught To Be Good Listeners Of Global Englishes Accents?mentioning
confidence: 99%
“…The intelligibility principle was new to most students, who nonetheless welcomed it as making more sense than native speakerism with the reality of globalized English. However, a phonetics course that mainly aimed to improve learners' speaker intelligibility did not greatly benefit Swedish students, who are already highly intelligible in international contexts (Jeong, 2019;Jeong et al, 2017Jeong et al, , 2020 (Kubota, 2001;Lindemann et al, 2016;, and seeing the needs for maximized listening comprehension of Global Englishes (Melchers, Shaw, Sundqvist, 2019), the emphasis of Jeong's teaching has shifted to fostering listener intelligibility for diverse English accents (Jeong, 2019).…”
Section: How It Startedmentioning
confidence: 99%